Internal fixation for fragility fracture of pelvis in a patient with ankylosing spondylitis. (December 2022) - Gamada, Hisanori; Yanagisawa, Yohei; Eda, Yusuke; Teruya, Shotaro; Yamazaki, Masashi
Abstract: Ankylosing spondylitis is a common inflammatory rheumatic disease with a prevalence of 0.1 %–1.4 %. The most common vertebral fractures associated with ankylosing spondylitis are cervical spine injuries due to low-energy trauma, whereas pelvic fractures are rare. Conversely, fragility fracture of the pelvis is a fracture of the pelvic ring caused by low-energy trauma with a background of bone fragility. In recent years, minimally invasive surgery for early mobilization of displaced fragility fracture of the pelvis has been reported. We report herein a case of a 91-year-old male with ankylosing spondylitis who underwent internal fixation for fragility fracture of his pelvis. He was brought to the emergency room with a complaint of pain in the right hip after a fall from a standing position at home. Computed tomography showed a fracture of the right pubis and a fracture, which crossed the sacrum from the ilium with a maximum dislocation. There was also extensive ossification of the anterior longitudinal ligament in the thoracolumbar spine and bony ankylosis of both sacroiliac joints. The diagnosis after the injury was fragility fracture of the pelvis, which complicated by ankylosing spondylitis. The fracture type did not match the Rommens and Hofmann classification criteria. Iliac intramedullary stabilization was performed in accordance with the treatment of Rommens and Hofmann classification type IIIa. The patient's pain reduced a day after the surgery, and he was able to use a wheelchair. He was able to walk with a cane two months after the surgery, and bone union was achieved four months postsurgery. Iliac intramedullary stabilization was useful in patients with atypical fractures a) that did not fit the Rommens and Hofmann classification criteria owing to the presence of ankylosing spondylitis, and b) in cases wherein strong fixation was considered necessary.